GIS–MCDA–based land suitability analysis for agrivoltaic development on degraded peatlands in South Sumatra - Muaffan Alfaiz Wisaksono (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
Degraded peatlands in South Sumatra experience drainage driven subsidence, recurrent fires, and seasonal flooding, yet they also have reliable long term solar resources, making them strong candidates for agrivoltaics that avoids conversion of intact peat. This study aimed to map and quantify agrivoltaic land suitability on degraded peatlands using an integrated GIS and multi-criteria decision analysis workflow. Eight criteria were prepared on a 30 m UTM Zone 48S grid and normalized to a 0 to 1 benefit scale: FRP weighted fire kernel density, peat depth class as a geotechnical proxy, flood hazard index, slope, distance to roads, aspect, topographic position index, and long term global horizontal irradiance. Weights were derived with the Analytic Hierarchy Process (CR= 0.00244) and combined using Weighted Linear Combination with protected areas applied as hard constraints. Across the eligible degraded peat domain (124,007.76 ha), 53.76% (66,665.25 ha) was very suitable and 24.89% (30,867.84 ha) was moderately suitable, while 19.68% (24,408.99 ha) and 1.67% (2,065.68 ha) were unsuitable and very unsuitable. Overall, 78.65% (97,533.09 ha) of eligible land was suitable or very suitable, indicating a substantial opportunity for policy-focused agrivoltaic screening on degraded peatlands while maintaining environmental safeguards.